Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1056/nejm199808063390601
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in New Metastases in Breast Cancer with Adjuvant Clodronate Treatment

Abstract: Clodronate can reduce the incidence and number of new bony and visceral metastases in women with breast cancer who are at high risk for distant metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
382
2
20

Year Published

1999
1999
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 751 publications
(419 citation statements)
references
References 26 publications
10
382
2
20
Order By: Relevance
“…This observation constitutes an important addition to the mechanistic understanding of how BPs, given in adjuvant setting, could prevent the development of bone metastases as shown by two clinical trials (Diel et al, 1998;Powles et al, 2002). Moreover, we attempted to elucidate whether this effect of ZOL could be explained by the inhibition of the MVA pathway, and more particularly by RhoA inactivation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This observation constitutes an important addition to the mechanistic understanding of how BPs, given in adjuvant setting, could prevent the development of bone metastases as shown by two clinical trials (Diel et al, 1998;Powles et al, 2002). Moreover, we attempted to elucidate whether this effect of ZOL could be explained by the inhibition of the MVA pathway, and more particularly by RhoA inactivation.…”
Section: Discussionmentioning
confidence: 95%
“…Two clinical trials of patients with breast cancer demonstrated that BPs, given in adjuvant setting, reduce the incidence of skeletal metastasis with a consequent improvement in survival (Diel et al, 1998;Powles et al, 2002). However, other authors reported opposite results (Saarto et al, 2001).…”
mentioning
confidence: 99%
“…In recent years bisphosphonates have become important in the management of cancer-induced bone disease and are now well established in the management of patients with multiple myeloma and bone metastases secondary to breast cancer (Paterson et al, 1993;Berenson et al, 1996;Hortobagyi et al, 1996;Diel et al, 1998;McCloskey et al, 1998;Theriault et al, 1999). Randomized controlled trials in patients with breast cancer have demonstrated that clodronate and pamidronate reduce skeletal morbidity and improve quality of life (Paterson et al, 1993;Hortobagyi et al, 1996;Kanis et al, 1996).…”
mentioning
confidence: 99%
“…Randomized controlled trials in patients with breast cancer have demonstrated that clodronate and pamidronate reduce skeletal morbidity and improve quality of life (Paterson et al, 1993;Hortobagyi et al, 1996;Kanis et al, 1996). Furthermore, in the adjuvant situation, studies with oral clodronate suggest that the use of bisphosphonates in combination with chemotherapy or endocrine therapy may delay first recurrence in bone (Diel et al, 1998). In addition, Diel et al have shown that treatment with oral clodronate may be associated with reduced rates of visceral metastases and improved survival compared with those receiving standard antineoplastic therapy alone (Diel et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation